Sustaining social security - United Nations Department for Economic and Social Information and Policy Analysis (New York : United Nations, 1997)
This text explores the central problems of social security and alternative solutions to them. Part one tackles conceptual problems of system design and governance, while part two examines how those problems have been approached in a selection of country situations.
"ST/ESA/251."
"United Nations publication sales no. E.97.IV.3"--T.p. verso.
Includes bibliographical references.
aia 2/9/16
Loans
Keywords: Social security; Sustaining social security